Model Penilaian Pemasok Bahan Olah Karet (Bokar) - Ridha Luthvina; Rika Ampuh Hadiguna; Jonrinaldi Jonrinaldi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2019)
Crumb rubber industry only depends on one main raw material that is called Bahan Olah Karet (Bokar). Based on the observation of several crumb rubber factories in West Sumatera, the company still uses an unsystematic way of choosing the suppliers of bokar. The weakening of the supplier’s supervision system causes bokar that received by the company, in terms of quality and quantity are not met properly. The way to solve these issues is to develop a fuzzy model for supplier assessment of bokar. The first step is the identification of criteria using FDM. Then developing a mathematical model. This research has been successfully developed a mathematical model where FAHP is used to determine the weight of supplier assessment criteria, combined with signed distance at the defuzzification stage. While FTOPSIS is used to obtain suppliers ranking. Through the survey using FDM, we obtain 6 main criteria and 18 subcriteria which relevant to the conditions of the crumb rubber industry in West Sumatera.